Revisiting damping identification: limitations and comparative evaluation under impulse, white noise, and seismic excitations - Zheng, Yuanqi; Lee, Chin-Long; Shen, Renjie; Guo, Jia (Frontiers in Built Environment, 2025)
Eigensystem Realization Algorithm (ERA), Stochastic Subspace Identification (SSI), Continuous Wavelet Transform (CWT), and Enhanced Frequency Domain Decomposition (EFDD) are four widely used damping identification methods. Their performance remains unclear in previous reviews and comparative discussions. This uncertainty can be attributed to three critical factors: the varying behavior of different methods under different excitations, the lack of a clear benchmark for evaluating accuracy, and the unquantified influence of parameter tuning on results. This study revisits and evaluates these methods under controlled conditions and addresses the key challenges that hinder reliable damping identification. A major challenge identified is the sensitivity of the results to parameter settings, which significantly impacts the stability and accuracy of the identification. Based on the evaluation, recommended methods and corresponding parameter guidelines are provided for three common excitation scenarios: impulse, white noise, and earthquakes. This study offers practical guidance for the selection and application of damping identification methods in structural dynamics.